AB-470. A double positive antibody: A case report on Guillain-Barré syndrome with positive anti-GT1a and anti-GQ1b ganglioside antibody - Alvin Oliver Payus; Tan, Hui Jan; Lee, Aik Kheng; Tan, Juen Kiem; Rabani Remli (Elsevier B.V., 2025)
Guillain-Barré syndrome (GBS) is an immune mediated peripheral polyneuropathy characterised by acute onset ascending symmetrical muscle weakness with or without bulbar involvement. Recently, anti-ganglioside antibodies played a major role in the pathophysiology and often closely related to the clinical phenotypes and specific manifestations of the condition. The presence of anti-GQ1b antibody is associated with ophthalmoplegia and ataxia in patient with Miller Fischer variant. This is because GQ1b gangliosides are densely localized in the paranodal regions of the oculomotor nerves and in the subpopulation of large neurons in the dorsal root ganglia. GT1a gangliosides on the other hand have been abundantly found in glossopharyngeal and vagal nerves. Therefore, monospecific anti-GT1a antibody which does not cross-react with anti-GQ1b was found to be highly related with bulbar palsy. However, anti-GQ1b and anti GT1a antibodies that cross-reactive to each other is not often reported. Here, we report a case of a case with predominant cranial nerves and sensory involvement and relatively sparring the motor component.